Paediatric targeted temperature management post cardiac arrest: A systematic review and meta-analysis. (June 2019) - Buick, Jason E.; Wallner, Clare; Aickin, Richard; Meaney, Peter A.; de Caen, Allan; Maconochie, Ian; Skifvars, Markus B.; Welsford, Michelle; ,; Meaney, Peter; Aickin, Richard; de Caen, Allan; et al.
Abstract: Introduction: The International Liaison Committee on Resuscitation prioritized the need to update the review on the use of targeted temperature management (TTM) in paediatric post cardiac arrest care. In this meta-analysis, the effectiveness of TTM at 32–36 °C was compared with no target or a different target for comatose children who achieve a return of sustained circulation after cardiac arrest. Methods: Electronic databases were searched from inception to December 13, 2018. Randomized controlled trials and non-randomized studies with a comparator group that evaluated TTM in children were included. Pairs of independent reviewers extracted the demographic and outcome data, appraised risk of bias, and assessed GRADE certainty of effects. A random effects meta-analysis was undertaken where possible. Results: Twelve studies involving 2060 patients were included. Two randomized controlled trials provided the evidence that TTM at 32–34 °C compared with a target at 36–37.5 °C did not statistically improve long-term good neurobehavioural survival (risk ratio: 1.15; 95% CI: 0.69–1.93), long-term survival (RR: 1.14; 95% CI: 0.93–1.39), or short-term survival (risk ratio: 1.14; 95% CI: 0.96–1.36). TTM at 32–34 °C did not show statistically increased risks of infection, recurrent cardiac arrest, serious bleeding, or arrhythmias. A novel analysis suggests that another small RCT might provide enough evidence to show benefit for TTM in out-of-hospital cardiac arrest. Conclusion: There is currently inconclusive evidence to either support or refute the use of TTM at 32–34 °C for comatose children who achieve return of sustained circulation after cardiac arrest. Future trials should focus on children with out-of-hospital cardiac arrest.